Extrapyramidal symptoms after exposure to calcium channel blocker-flunarizine or cinnarizine - Jhang, Kai-Ming; Huang, Jing-Yang; Nfor, Oswald Ndi; Tung, Yu-Chun; Ku, Wen-Yuan; Lee, Chun-Te; Liaw, Yung-Po (European journal of clinical pharmacology, 2017)
Purpose Flunarizine (fz) and cinnarizine (cz) have well-known extrapyramidal side effects (EPSEs). The aim of this study was to evaluate the incidence and occurrence time of cz- and fz-related EPSEs. Method Patients who took fz or cz for more than 1 month were identified from the longitudinal health insurance database 2005 and 2010. Excluded were patients with any of the underlying diseases that may cause parkinsonism. Drug-induced EPSEs were defined as the new diagnosis of parkinsonism, dyskinesia, or secondary dystonia during drug use or within 3 months after discontinuing the medication. Age- and sex-matched controls were included in this study. Results Recruited for analysis were individuals who took fz ( n = 26,133) and cz ( n = 7186). The incidence rates of fz- and cz-induced EPSEs were 21.03 and 10.3 per 10,000 person-months, respectively. The hazard ratios (HRs) of EPSEs among fz and cz subjects were 8.03 (95% CI 6.55–9.84) and 3.41 (95% CI 2.50–4.63) when compared with the control individuals. Both fz and cz patients had a higher cumulative incidence of EPSEs than their control individuals ( p < 0.001). Among subjects who took fz, the incidence of EPSEs was higher in the second than first year of drug exposure (45.59 vs 21.03 per 10,000 person-months). Conclusions Fz and cz significantly increased the risk of parkinsonism, dyskinesia, and dystonia. Potential benefits and risks should be weighed when considering long-term use of these drugs especially fz.